PARAVERTEBRAL SEGMENTAL SKIN SYMPATHETIC REACTIONS IN HEALTH PEOPLE AND IN PATIENTS WITH DORSOPATHIES - I. V. Boitsov (Acta Biomedica Scientifica, 2012)
The aim. of the research was to prove and develop methodology of use of dynamic segmental diagnostics as the way of testing of skin sympathetic reactions during complex examination of patients with dorsopathies. We examined, patients with injuries of intervertebral discs of cervical, thoracic and. lumbar segments of spine, with dorsalgies on the background, of neurological manifestations of spinal osteochondrosis: 151 male and. 165 females (from 17 to 62 years) and 67 healthy people (27 males and 40 females (from 14 to 29 years). We summarized data of the intensity of skin sympathetic reactions in paravertebral segmental zones of different segments of spine and showed dependence of these reactions' intensity on the character of injury of vertebromotor segments at the dorsopathies.